Menjaga Keberlangsungan Umkm Pada Masa Wabah Covid-19 - Moh. Ubaidillah (Universitas PGRI Madiun, 2020)
This study aims to determine and obtain empirical evidence about the effect of governance and human resources on the sustainability of UMKM during the Covid-19 outbreak. Sampling in this study used a purposive sampling method which resulted in a sample of 100 UMKM actors in Magetan district. The method of data analysis in this research is using Structural Equation Modeling (SEM) analysis with Partial Least Squares (PLS). The results showed that governance had a positive effect on the sustainability of UMKM during the Covid-19 outbreak. Furthermore, human resources have a positive effect on the sustainability of UMKM during the Covid-19 outbreak.Keywords; UMKM Sustainability; Governance; Human Resources